An unusual ultrasonographic manifestation of a fetal Ebstein anomaly - Cha, Min-Young (Obstet Gynecol Sci, 2014)
An Ebstein anomaly is a rare congenital heart defect defined by an inferior displacement of the septal and posterior leaflets of the tricuspid valve from the tricuspid annulus. This anomaly shows various ultrasonographic manifestations, thus making the prenatal diagnosis sometimes difficult. We here report a rare case of an Ebstein anomaly which was prenatally suspected as the absence of the tricuspid valve with functional pulmonary atresia because of non-visible tricuspid leaflets on an echocardiograph at 24 weeks of gestation. An emergency cesarean section was performed at 35 weeks of gestation as fetal hydrops were seen on a follow-up scan. Postnatal surgery confirmed Ebstein anomaly type-D which demonstrates an almost complete atrialization of the right ventricle with the exception of a small and infundibular component. Because of its rarity, prenatal findings of a type-D Ebstein anomaly have not been reported previously. We suggest from this first such case report that this anomaly should be considered as a possible diagnosis when the tricuspid leaflets are not well visualized.